Analysis of Employee Satisfaction in Non-Profit Organisations: Based on a Survey of an Association in Nanjing City - Li, Xiang (International Journal of Social Sciences and Public Administration, 2024)
Since the beginning of the 21st century, with the gradual expansion of the non-profit organization team, its related needs in human resource management have become increasingly urgent. And the related research on human resource management in non-profit organizations has gradually attracted attention. However, compared with the more mature research on human resource management in for-profit organizations, there are relatively few studies on human resource management in non-profit organizations. This paper selects employee satisfaction as the starting point to study the human resource management of non-profit organizations. Employee satisfaction, as one of the dimensions for judging the human resource management level of non-profit organizations, can detect problems in the human resource management of the organization as early as possible and make corresponding improvements to meet the needs of employees and enhance their work enthusiasm. At the same time, employee satisfaction can also predict employees’ mobility intentions and become an important reference for preventing brain drain in advance. This research is based on the relevant theory of job satisfaction, using a questionnaire survey and in-depth interviews as research methods. Take an association in Nanjing as an example to conduct field research and analysis on employee satisfaction in non-profit organizations. In-depth analysis, using SPSS software to carry out descriptive statistical analysis on the data collected by the questionnaire survey and test the reliability and validity of the questionnaire results, found the shortcomings of human resource management in non-profit organizations. Through relevant theoretical analysis, taking into account the actual situation of the association, it puts forward corresponding improvement measures and suggestions for the human resource management of non-profit organizations.